Nieestetyczne zachowania jako technika autoprezentacji w mediach masowych = Unaesthetics of behaviour as a technique of self-presentationin mass media - Tyc, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The contemporary television is constantly seeking an audience. This is ensured by continuous professionalisation of television shows, being at the centre of events at home and abroad as well as persuasiveness of messages. It is also a medium that has a power to distinguish. This article describes statements and behaviour of public figures in a television studio. This analysis has revealed that aesthetics is an art of self-presentation reflecting communication skills of a speaker.
Keywords: telewizja; estetyka językowa; estetyka zachowania; nieestetyczne zachowania; magazyn informacyjno-publicystyczny; autoprezentacja; television; language aesthetics; behaviour aesthetics; behaviourunaesthetics; information and commentary magazine; self-presentation